Thermal comfort in colonial and modern school buildings / Syed Hazlan Izham Syid Abdullah - Syid Abdullah, Syed Hazlan Izham (2004)
This research is to measure the comfort level at colonial and modern schools in Klang Valley area. Three schools were selected for each type. Colonial schools were represented by Victoria Institution, St. John Institution and Methodist Boys School. For the modern type schools, they are represented by Sekolah Agama Menengah Bestari Jais USJ 5, Sekolah Menengah Kebangsaan USJ 4 and Sekolah Menengah Kebangsaan Seafield. The thermal comfort level measurement is carried out using the Comfy Meter instrument and all the result will be calculated by Comfy Meter software and presented in table and graph forms in NEC laptop computer. Then, all the data are transferred into more compact form as can be seen in Chapter 6. In achieving the objectives of this study, both internal and external aspect for each school are takerrinto accountTThe comfort level instrument measured internal comfort level (all fans are being switched off) and then the results are analysed with consideration of surrounding area of the schools. The final result showed that the St. John Institution is the best and the most comfort to study followed by Sekolah Agama Menengah Bestari Jais and the-Methodist Boys School is in the last position. St. John Institution has an average of Predicted Mean Vote (PMV) rating 1.2, which is slightly warm that gives Predicted Percentage of Dissatisfied (PPD) 35 percent while Methodist Boys School has an average of PMV rating 2.2, which is warm that gives PPD 81 percent.